Pengaruh penggunaan media video terhadap motivasi dan hasil belajar kognitif pembelajaran IPA kelas V - Corry Pebriani (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2017)
Penelitian ini bertujuan untuk mengetahui: (1) pengaruh media video terhadap motivasi belajar peserta didik pada pembelajaran IPA, (2) pengaruh media video terhadap hasil belajar kognitif peserta didik pada pembelajaran IPA, (3) pengaruh media video terhadap motivasi belajar dan hasil belajar kognitif peserts didik pada pembelajaran IPA. Penelitian ini adalah quasi experiment. .Populasi penelitian ini adalah peserta didik kelas V se gugus 04 Palangka Raya. Sampel penelitian ditentukan dengan teknik cluster random sampling. Pengumpulan data menggunakan skala motivasi dan tes. Pengujian hipotesis dengan teknik MANOVA. Penelitian ini membuktikan bahwa terdapat pengaruh positif pada pembelajaran IPA yang menggunakan media video dibandingkan dengan pembelajaran IPA yang menggunakan media gambar terhadap motivasi belajar dan hasil belajar kognitif pembelajaran IPA.Kata kunci: media video, motivasi belajar, hasil belajar kognitif. The effect of video media on learning motivation and learning outcomes in natural science subject of the fifth grade students of elementary schoolsAbstractThis research aims to describe: (1) the effects of the video media on students’ learning motivation related to the natural science subject; (2) the effects of the video media on students’ cognitive learning outcomes related to the natural science subject; (3) the effects of the video media on students’ learning motivation and cognitive learning outcomes related to the natural science subject. This research is a quasi experiment. The population was the students of Fifth Grade Students of Elementary Schools Location 04 Palangka Raya. The sample was established using the cluster random sampling technique. The data collection used a motivation scale and test. The hypotesis testing used the MANOVA. The result of the research shows that there to know the difference of learning motivation and cognitive learning result in natural science subject of the fifth grade students of elementary schools location 04 Palangka Raya between before and after using video media.Keywords: video media, learning motivation, cognitive learning result.